Á̂n tượng Thăng Long - Hà Nội - Bùi, Việt M~y. (Hà Nội : Nhà xuá̂t bản Lao động, 2005)
History of land and civilization of Hanoi, Vietnam.
Includes bibliographical references.
Keywords: Hanoi (Vietnam)